Development of UV 3D-Printing Resin Using Polyhydroxybutyrate and Low-Methoxyl Pectin From Durian Rind - Zaini, Nur Alia Syamira; Muhammad Fuzi, Siti Fatimah Zaharah (Enhanced Knowledge in Sciences and Technology, 2025)
Durian rind is often discarded as agricultural waste, contributing to environmental issues. Furthermore, the use of biodegradable materials in 3D printing may lead to sustainable and recyclable items. Pectin’s high gel-forming ability, biodegradability, and biocompatibility make it an ideal biopolymer. The purpose of this study is to extract and characterize low-methoxyl pectin (LMP) from durian rind for potential use in UV 3D printing. The methoxyl content of pectin extracted from durian rind is 1.37 ± 0.601%. The resulting resin is then exposed to UV light and analyzed using FTIR to confirm polymer formation and functional group changes. The resin commercial exhibits minor changes in functional groups, such as a slight decrease in the intensity of O-H and N-H stretching peaks 3440 to 3507 cm⁻¹ change 3437 cm⁻¹ range after exposure to UV light and a change in the C-O 1271–1059 cm⁻¹ range stretching band from 1256 to 1062 cm⁻¹ after UV exposure comparing the resin formulation remains had same peak even after UV exposure, with no significant changes in its functional groups.